Literary review of public relations in libraries in a global perspective - Lusiana, Elnovani; Perdana, Fitri; Khadijah, Ute Lies Siti; Nursari, Tita (Universitas Padjadjaran, 2025)
The era of globalization is increasingly developing, and the role of public relations is crucial to build a positive image and increase the relevance of libraries in the public point of view. This study aimed to determine how public relations programs in libraries in a global perspective through an analysis of optimizing library public relations strategies, maximizing projects to build optimal public relations strategies, and implementing effective library public relations strategies. The study used a literature review, highlighting the primary functions of public relations in promoting services, fostering relationships with the community, and increasing user participation. The results of the study indicated that the right public relations strategy maintained a positive impact on libraries amidst global competition and cultural diversity of users. Decision making based on user analysis, adaptation to trends, opening information as openly as possible and adopting technology, developing advanced programs as a library identity, and creating segmented programs were ways to optimize public relations projects. Libraries that were able to execute public relations programs optimally showed an increase in visits and were able to sustain their existence and relevance in this global era. The concludes that public relations is a program that libraries need to emphasize and improve, and librarians are the key factor in maximizing public relations programs so that the library’s role in the community can be more effective and impactful.